Problems of measurement of temperature and temperature field in the study of free jets - Толеуов, Г.; Сейтжaппaровa, A.; Жетибaй, Г.; Сериковa, A.; Рустемовa, С.; Есенaлинa К., К. (Recent Contributions to Physics, 2016)
The experimental setup allowed to conduct research of three-dimensional turbulent jets, based on the characteristics measurement dynamic, thermal characteristics jets. A flow rate varied between the limits 6÷15 m/s. A flow temperature varied from room temperature to 600 C. Preliminary measurements have shown that the shape of the transverse profiles in both axes of symmetry of the nozzle close to a uniform distribution, there are only small areas rather irregularly in the corresponding heat dissipation from the outer sides of the nozzle. For this reason, the outer sides of the rectangular nozzles possible heat insulated from the environment. It is necessary to reduce to a minimum deviation from the rectangular shape by cross sections of temperature at the nozzle exit. In the course of the experiments carried out data correction by constructing a calibration curve to calculate the values of temperature. Moving the recorder on the y coordinate was relatively calibrate mercury thermometer readings. Studies aerodynamics and heat transfer processes three-dimensional turbulent jets performed in a wide range of geometric parameters of the nozzle, and a flow rate of the initial parameters of the control action.